An ethical challenge: Towards digital healthcare - Petralia, Paolo; Ciliberti, Rosagemma (Medicina Historica, 2023)
The progressive and continuous advancement of new technologies and digital ecosystems, together with a growing expertise in analyzing and interpreting big data, artificial intelligence, and machine learning tools, increasingly enables personalized and effective therapeutic responses. This evolution holds promises of more targeted treatments tailored to individual needs. However, the significant technological challenges of today and the future demand an ethical approach capable of ensuring that as technology evolves, it is applied in a manner that respects humanity, which should remain the ’end’ and not the ’object’ of innovation. The concept of ’techno-humanism’ emerges as a bridge, a vital connection between the potential of technology and the intrinsic value of humanity. This philosophy can ensure a responsible translation of technology into practice, upholding principles of fairness in accessing medical innovations and ethical considerations in decision-making processes.